The Specificity of French Folk Tales - Norova Mokhitobon Fayzulloevna (Indonesian Journal of Innovation Studies, 2022)
The work is devoted to the analysis of the features of French folk tales. The author considered the concept of "fairy tale". The article defines the mainfeatures of French folk tales at the lexical, syntactic levels, in particular, the emphasis is on the morphology of the folklore text. On the basis of the study, the author analyzed the sequence of the main functions of characters, traditional formulas, revealed the presence of realities inherent in French folk tales.